Composite Mn–Co electrode materials for supercapacitors: why the precursor's morphology matters!. Issue 23 (31st October 2022) - Invernizzi, Ronan; Lemoine, Alexia; Madec, Lénaïc; Weill, François; Dourges, Marie-Anne; Tang, Céline; Giaume, Domitille; Baraille, Isabelle; Taberna, Pierre Louis; Flahaut, Delphine; Olchowka, Jacob; Guerlou-Demourgues, Liliane
Abstract : This work demonstrates how the size and morphology of the precursor building blocks influence their nanoscale distribution homogeneity within the final composite. Abstract : In the energy storage field, an electrode material must possess both good ionic and electronic conductivities to perform well, especially when high power is needed. In this context, the development of composite electrode materials combining an electrochemically active and good ionic conductor phase with an electronic conductor appears as a perfectly adapted approach to generate a synergetic effect and optimize the energy storage performance. In this work, three layered MnO2 phases with various morphologies (veils, nanoplatelets and microplatelets) were combined with electronic conductor cobalt oxyhydroxides with different platelet sizes (∼20 nm vs. 70 nm wide), to synthesize 6 different composites by exfoliation and restacking processes. The influence of precursors' morphology on the distribution of the Mn and Co objects within the composites was carefully investigated and correlated with the electrochemical performance of the final restacked material. Overall, the best performing restacked composite was obtained by combining MnO2 possessing a veil morphology with the smallest cobalt oxyhydroxide nanoplatelets, leading to the most homogeneous distribution of the Mn and Co objects at the nanoscale. More generally, the aim of this work is to understand how the size and morphology of the precursor building blocks influence their distribution homogeneity within the final composite and to find the most compatible building blocks to reach a homogeneous distribution at the nanoscale.